Direct ink writing of Si2N2O porous ceramic strengthened by directional β-Si3N4 grains. Issue 10 (July 2020) - Jin, Haize; Jia, Dechang; Yang, Zhihua; Zhou, Yu
Abstract: Porous Si2 N2 O ceramics strengthened by directional β-Si3 N4 are fabricated by direct ink writing technique and seeding method. Slurries prepared with different contents of β-Si3 N4 grains exhibited superior printing behavior. The degree of orientation of β-Si3 N4 grains increased with the increase of grains content. The mechanical properties of the porous Si2 N2 O ceramic are effectively improved by interspersed β-Si3 N4 grains and present anisotropy. This novel strategy provides a reference for fabricating high-performance anisotropic complex structure ceramics.